APPLICATION OF MULTISIM AND LTSPICE SOFTWARE PACKAGES TO SIMULATE THE OPERATION OF ELECTRONIC COMPONENTS AS AN ALTERNATIVE TO MEASUREMENTS OF REAL ELEMENTS - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper presents the process of carrying out simulations of the operation of electronic elements by means of software packages Multisim and LTspice. Using the software, students can test a possibility of replacing real measurements by results obtained from a simulation. The can reach the relevant conclusions by comparing the results and analysing the data obtained. In this way students gain experience needed for carrying out a didactic project in a creative way.